Breastfeeding Initiation and Duration in First-Time Mothers: Exploring the Impact of Father Involvement in the Early Post-Partum Period - Theresa Hunter; Georg'ann Cattelona (Tabriz University of Medical Sciences, 2014)
Background: The early post-partum period is a crucial time for breastfeeding support. Mothers who have physical and emotional support during this period are more likely to be successful in breastfeeding. This study examined the relationship between father involvement and support for breast feeding initiation and duration in first-time mothers. Methods: Overall, 146 women who attended a childbirth education class or breastfeeding course at BABS were asked to fill out the Childbirth Experiences Survey, which explored key topics such as (1) breastfeeding initiation, (2) early post-partum breastfeeding, (3) breastfeeding plan, (4) post-partum breastfeeding support and (5) breast feeding duration. This was a voluntary self-reported questionnaire. The surveys were completed by the mothers during the post-partum period. Results: 45.9% (n=67) of mothers received helped from their husband or partner with breastfeeding while in the hospital, while 54.1% (n=79) of mothers did not receive support from their partners. Mothers who received early post-partum breastfeeding support were more likely to continue breastfeeding after leaving the hospital. Conclusion: First-time mothers who identified as having breastfeeding support from their partners, the infant's father, during the early post-partum period were more likely to initiate breastfeeding and had longer breastfeeding durations.